2010
DOI: 10.1007/s10439-010-9979-4
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Strain as a Regulator of Mesenchymal Stem Cell Osteogenesis

Abstract: A role for mechanical stimulation in the control of cell fate has been proposed and mechanical conditioning of mesenchymal stem cells (MSCs) is of interest in directing MSC behavior for tissue engineering applications. This study investigates strain-induced differentiation and proliferation of MSCs, and investigates the cellular mechanisms of mechanotransduction. MSCs were seeded onto a collagen-coated silicone substrate and exposed to cyclic tensile mechanical strain of 2.5% at 0.17 Hz for 1-14 days. To exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 61 publications
4
104
0
2
Order By: Relevance
“…Also we tested the downstream effects of stretching on mineralized matrix formation. It has been shown that mechanical stimulation leads to increased matrix deposition [32,47]. deposit less matrix when mechanically stimulated compared to non-stressed Nf1(ob-/-) cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also we tested the downstream effects of stretching on mineralized matrix formation. It has been shown that mechanical stimulation leads to increased matrix deposition [32,47]. deposit less matrix when mechanically stimulated compared to non-stressed Nf1(ob-/-) cells.…”
Section: Resultsmentioning
confidence: 99%
“…In this model, the Nf1 gene has been knocked-out using the Cre-LoxP system under the control of 2.3 kb collagen1-alpha1 promoter (Col11), which is primarily expressed in osteoblast [23,25]. Our current view of the NF1 bone pathology, based on the analysis of osteoblast function, whether the imbalance of bone homeostasis and improper response of osteoblast cell to mechanical stress cause the NF1 skeletal manifestations [26][27][28][29][30][31][32][33][34][35].…”
Section: Signaling In Nf1 Osteoblast Cellsmentioning
confidence: 99%
“…As with other methods, tension is applied cyclically (typically 1 Hz) to induce changes within the cells, 51 using strain magnitude (5-10%) similar to compressive loading. 67,68 …”
Section: D Compressionmentioning
confidence: 99%
“…64,65 or (e) strain. 67,68 In vitro loading of bone-derived cells RM Delaine-Smith et al A summary of the mechanical stimuli described is provided in Table 1.…”
Section: D Models For Loading Osteocyte-osteoblast Coculturesmentioning
confidence: 99%
“…ASCs secrete osteoinductive growth factors, which may contribute to bone formation by recruiting host bone-forming cells or stimulating angiogenesis when implanted in vivo (Hao et al 2010;Scherberich et al 2010). Stretch-activated cation channels interpret mechanical strain in osteoblasts (Kearney et al 2010). One hypothesis is that forces acting on cells change protein conformation, exposing binding sites in a functionally relevant way (Teo et al 2010).…”
Section: Indirect and Chemical Mechanisms: Receptors Ion Channels Gmentioning
confidence: 99%